DIGITALIZATION OF KEY PROCESSES IN THE WOOD PROCESSING COMPANIES - Dražana Gašpar; Ivica Ćorić; Mirela Mabić (Economic Review)
The wood processing industry is not immune to the ripple effects of information technology's constant and rapid growth. Companies from that industry are under more pressure than ever to use digital innovation to adapt to rapidly shifting markets, lead the charge in the energy transition, and speed up the implementation of Industry 4.0. The paper presents research on the digitalization of key processes in the wood processing companies that are members of the "Herzegovina" wood cluster. Questionnaires and interviews are used to obtain research data. According to the research findings, there is a difference in the degree of digitalization between the interior planning and design process, which has the highest level of digitalization, and the cutting, hauling, and transportation of lumber, which has the lowest level of digitalization. The findings show that, regardless of the process in issue, the formal environment for digitalization must be established by declaring digitalization as a strategic goal, redefining roles and responsibilities, and ensuring a constant financial flow.